Propuesta de Guía Para intervenir en procesos de justicia restaurativa con perspectiva de género: Herramientas desde la academia para personas facilitadoras - Lecumberri, Paz Francés (Revista de victimología, 2025)
This article proposes a guide for intervening in restorative justice processes with a gender perspective, aimed at professional facilitators. Throughout the text, the challenges and opportunities of integrating gender into restorative processes are discussed, highlighting the need for a multidimensional approach that considers structural inequalities and power dynamics. Additionally, specific strategies and protocols are included to ensure an equitable intervention environment, with the goal of preventing secondary victimization, revictimization and promoting empowerment for those affected.The importance of gender training for facilitators and the inclusion of measures to assess and ensure the effectiveness of the processes are emphasized.